2018
DOI: 10.3389/fphar.2018.01171
|View full text |Cite
|
Sign up to set email alerts
|

Novobiocin, a Newly Found TRPV1 Inhibitor, Attenuates the Expression of TRPV1 in Rat Intestine and Intestinal Epithelial Cell Line IEC-6

Abstract: Background and Purpose: Novobiocin (NOVO), an ABC transporter inhibitor, decreases intestinal wall permeability of capsaicin (CAP), an ABC transporter substrate. However, the mechanism of this effect is not consistent with the action of NOVO as an ABC transporter inhibitor. We previously found that CAP can also be transported via TRPV1, which was site-specific in the permeability of CAP across the intestine. We explored the regulation by NOVO of TRPV1 in the present study.Methods: Rats and transfected IEC-6 ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
0
4
0
1
Order By: Relevance
“… 27 However, Zhang et al revealed that CAT and capsaicin both increased TRPV1 protein expression; 18 Liang et al also showed that capsaicin increased the TRPV1 protein expression in jejunum, ileum and colon, while novobiocin, a Newly Found TRPV1 Inhibitor, decreased the TRPV1 protein expression. 28 In this study, we found that CAT promoted, while JNJ inhibited the TRPV1 expression during intestinal I/R.…”
Section: Discussionmentioning
confidence: 54%
“… 27 However, Zhang et al revealed that CAT and capsaicin both increased TRPV1 protein expression; 18 Liang et al also showed that capsaicin increased the TRPV1 protein expression in jejunum, ileum and colon, while novobiocin, a Newly Found TRPV1 Inhibitor, decreased the TRPV1 protein expression. 28 In this study, we found that CAT promoted, while JNJ inhibited the TRPV1 expression during intestinal I/R.…”
Section: Discussionmentioning
confidence: 54%
“…Liang et al reported the inhibition by NVB of TRPV1-mediated CAP transport across the intestine wall in a dose-dependent manner . Moreover, NVB down-regulated TRPV1 expression in the intestine as confirmed by qRT-PCR and western blot experiments.…”
Section: Resultsmentioning
confidence: 81%
“…Therefore, TFEB is involved in Caps-mediated transcription of autophagy genes, resulting in the enhanced intracellular killing of S. flexneri . Moreover, capsaicin is known to selectively bind to the TRPV1 receptor and induce calcium influx ( Liang et al, 2018 ; Allais et al, 2020 ). TRPV1 is expressed in intestinal cells and is known to induce autophagy ( Chen et al, 2021 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%